2014
DOI: 10.1016/j.ppnp.2014.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Overview of neutron–proton pairing

Abstract: The role of neutron-proton pairing correlations on the structure of nuclei along the N = Z line is reviewed. Particular emphasis is placed on the competition between isovector (T = 1) and isoscalar (T = 0) pair fields. The expected properties of these systems, in terms of pairing collective motion, are assessed by different theoretical frameworks including schematic models, realistic Shell Model and mean field approaches. The results are contrasted with experimental data with the goal of establishing clear sig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
183
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(184 citation statements)
references
References 185 publications
(668 reference statements)
1
183
0
Order By: Relevance
“…[15]. It should be noted that for 113 Cs with neutron number N = Z + 3, the neutron-proton pairing correlations may play an important role on the properties of rotational alignments in the high-j proton and neutron h 11/2 subshell [65,66]. After considering this effect, the calculated results may be improved.…”
Section: Numerical Detailsmentioning
confidence: 99%
“…[15]. It should be noted that for 113 Cs with neutron number N = Z + 3, the neutron-proton pairing correlations may play an important role on the properties of rotational alignments in the high-j proton and neutron h 11/2 subshell [65,66]. After considering this effect, the calculated results may be improved.…”
Section: Numerical Detailsmentioning
confidence: 99%
“…A detailed review can be found in Ref. [9]. Here we mentioned a few studies around the same region as we studied above.…”
Section: The Np Pairing Correlation Within the Deformed Shell-model Fmentioning
confidence: 99%
“…Overviews on np pairing correlations are published recently in Refs. [9,10,11]. Extensive discussions can also be found in workshops organized recently (see, e.g., Ref.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…This led to a renewal of interest in neutronproton (np) pairing (see e.g. [1]). The latter is often treated using the BCS theory of which the main defect is the non-conservation of the number of particles.…”
Section: Introductionmentioning
confidence: 99%